PELAKSANAAN TUGAS POKOK DAN FUNGSI BAGIAN PERSIDANGAN PADA DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN SIJUNJUNG - Eva Suryany; Marwandizal -; Watra Gema Febryanda (Jurnal Public Administration, Business and Rural Develoment Planning, 2022)
The objectives of this study are 1.To find out the implementation of the main tasks and functions of the trial section of the Sijunjung Regency DPRD. 2.To find out the factors that influence the implementation of the main tasks and functions of the trial section of the DPRD Sijunjung Regency. In this study, the authors used descriptive research methods with a qualitative approach, and data collection techniques using a. Observation, interview, documentation and analysis of literature. From the findings of the research and discussion, the following conclusions and suggestions are obtained: 1. The Trial Section at the Secretariat of the Sijunjung Regency DPRD has tried to provide administrative services to the institutional council in terms of court services but in practice it is still felt to be lacking by the Council Members served so that it requires work improvements. services to be able to realize the vision of the DPRD Sijunjung Regency. 2. Of the factors that affect the service by the field of trial, there are still employees who do not show a sense of responsibility for their work and office regulations, such as taking undisciplined actions. Services provided by Secretariat employees, which are considered to be lacking, can be a problem that interferes with good service. It is necessary to improve the quality of employee work, in addition to training or technical guidance, it can be done by more frequent leadership in providing directions to employees, so that employees feel cared for by the leadership, besides that, direct assessments can also be carried out from the leadership to employees, so that employees are more motivated to improve the quality of their work 2. Rolling of employees per section by taking into account the educational background and expertise of employees, the leadership should be more frequent in giving directions or briefings, so that the communication process can be open, so that employees also become more compact and solid